(untitled) (The Pretoria Student Law Review, 2021)
It has been over two decades since apartheid, which was declared a crime against humanity, ended. A Truth and Reconciliation Commission (hereafter TRC) was established in 1995 with the hopes of, amongst other things, promoting national unity and reconciliation.1 Whilst the TRC received many criticisms, it was also praised for promoting national unity and reconciliation. However recent social media posts which were seen as racist have shattered the picture of a reconciled nation free from racism.2 The government’s response to these manifestations of racism is of particular interest in this article. The government wants to enact legislation to criminalise racism as a way to not only deter, but to eradicate racism.3 In this article I will be critically analysing the law’s ability to eradicate racism and ultimately argue that while legislation may address individual discriminatory acts, it fails to address racism as a structural power system. I will do this by firstly determining the success of the TRC in achieving national unity and reconciliation. Secondly, I will briefly analyse post-apartheid South Africa through Antjie Krog’s book ‘A change of tongue’. Lastly, I will critically discuss the need to utilise a Critical Race Theory and African Jurisprudence in post-apartheid South Africa.